A method for preparing metal organic framework membrane using cryogenic reverse diffusion technology

By using frozen counter-diffusion technology to control the release and diffusion of metal ions or organic ligands in the porous carrier, the problems of continuity and process complexity of MOF membrane are solved, and the good convergence and excellent separation performance of MOF membrane are achieved.

CN115945080BActive Publication Date: 2025-02-28DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310004974.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-04
Publication Date
2025-02-28
Estimated Expiration
2043-01-04

AI Technical Summary

Technical Problem

In conventional reverse diffusion processes, the growth range of MOF crystals is relatively wide, which affects the continuity of the MOF film and is complicated in the preparation process.

Method used

Refrigeration counter-diffusion technology is used to freeze the metal source solution or organic ligand solution in the porous carrier to control the release and diffusion of metal ions or organic ligands and increase the MOF nucleation density.

Benefits of technology

The MOF membrane is achieved with good convergence properties, excellent separation performance, thermal stability, chemical stability and mechanical stability, while simplifying the process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a metal organic skeleton membrane by using a freezing reverse diffusion technology, wherein a metal source solution is frozen inside a porous carrier and reacted with an organic ligand solution; or an organic ligand solution is frozen inside a carrier and reacted with a metal source solution; after the reaction is completed, the metal organic skeleton membrane is obtained by washing and drying; the freezing temperature is ‑196 to ‑20°C; and the organic ligand solution or the metal source solution includes a reaction aid. The MOF membrane prepared by the present invention is dense and continuous, has a thin effective membrane thickness, excellent stability, and good gas separation performance; at the same time, the preparation process is simple, the cost is low, the universality is strong, and it has good industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane separation, and in particular relates to a method for preparing a metal organic skeleton membrane using a freezing reverse diffusion technology. Background Art

[0002] The chemical separation process is one of the most energy-intensive steps in the chemical industry. Traditional separation technologies such as distillation separation involve phase transitions, which results in huge energy consumption and complex operations, as well as high operating costs. Compared with traditional separation technologies, membrane separation technology, as an emerging separation method, has attracted widespread attention for its energy-saving, high efficiency, environmental friendliness, simple equipment, and high integration.

[0003] Metal organic framework (MOF) has become an ideal membrane material for efficient separation based on differences in molecular size, shape or polarity due to its high specific surface area, wide range of pore sizes and rich functional groups. It has shown excellent application prospects in gas separation, organic matter removal, pervaporation, ion sieving and desalination. The preparation process of MOF molecular sieve membranes is developing rapidly. At present, liquid phase synthesis method is widely used to prepare MOF membranes, but because of the low heterogeneous nucleation density, it is usually necessary to pre-modify the active transition layer or seed layer on the surface of the carrier, which complicates the membrane preparation process. The reverse diffusion method is an effective method for in situ preparation of MOF membranes. By placing the precursor solution containing metal ions and organic ligands on both sides of the porous carrier, MOF crystals preferentially nucleate and grow at the interface between the carrier and the solution under the action of the concentration gradient. One advantage of this method is that the reaction between metal ions and ligands is more controllable, so the nucleation and growth kinetics of MOF crystals in the bulk solution can be more accurately controlled, thereby achieving a higher nucleation density on the carrier surface. However, in the conventional reverse diffusion process, the reaction phase interface is affected by the difference in the reaction rate of metal ions and organic ligands and the diffusion rate of the reactants, resulting in a wider growth range of MOF crystals, which in turn affects the continuity of the MOF film. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing a polycrystalline MOF membrane on a porous carrier using a cryogenic reverse diffusion technique. The MOF membrane prepared by the method has good intergrowth, excellent separation performance, excellent thermal stability, chemical stability and mechanical stability. At the same time, the preparation method is simple in process, low in cost, and has strong universality, and has good industrial application prospects.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a metal organic skeleton membrane by using a freezing reverse diffusion technology, comprising: filling a metal source solution inside a porous carrier, freezing the solution, and reacting with an organic ligand solution; or filling an organic ligand solution inside a porous carrier, freezing the solution, and reacting with a metal source solution; after the reaction is completed, the metal organic skeleton membrane is obtained by washing and drying; the freezing temperature is -196 to -20°C; the organic ligand solution or the metal source solution also includes a reaction aid.

[0007] The solvent in the organic ligand solution or the metal source solution is water, methanol, ethanol, N,N-dimethylformamide, N,N-diethylformamide, dimethyl sulfoxide or propanol.

[0008] The freezing method is rapid freezing or slow freezing, and the freezing time is 1 minute to 120 hours; rapid freezing is preferably liquid nitrogen freezing, and slow freezing is preferably refrigerator freezing or low-temperature alcohol bath freezing.

[0009] The metal element in the metal source is zinc, magnesium, zirconium, iron, cobalt, aluminum, nickel or copper.

[0010] The organic ligand is an imidazole, carboxylic acid or pyridine ligand.

[0011] The molar ratio of the organic ligand to the metal source is organic ligand / metal source=0.1-5.

[0012] The reaction aid is an alkaline or acidic reagent, preferably potassium hydroxide, sodium hydroxide, sodium acetate, ammonia water or acetic acid.

[0013] The molar ratio of the reaction aid to the metal source is reaction aid / metal source=0.01-1.

[0014] The reaction temperature is 20-180° C., and the reaction time is 1 min-120 h. The heating method is convection heating or microwave heating. The convection heating is oven heating or oil bath heating. The microwave heating is single-mode microwave heating or multi-mode microwave heating.

[0015] The drying temperature should not be higher than the pyrolysis temperature of the MOF material.

[0016] The porous carrier is of sheet, tube or hollow fiber type; the porous carrier is of porous metal oxide, porous metal or porous non-metal oxide; the porous metal oxide is porous aluminum oxide, porous titanium oxide or porous yttrium oxide, the porous metal is porous stainless steel or porous nickel, and the porous non-metal oxide is porous silicon oxide, porous silicon carbide or porous glass.

[0017] The present invention also provides the metal organic framework membrane in CO 2 / N 2 , CO2 / CH 4 , C 2 H 4 / C 2 H 6 , C 3 H 6 / C 3 H 8 、nC 4 H 10 / iC 4 H 10 , O 2 / N 2 , H 2 / CO 2 or H 2 / CH 4 Separation application.

[0018] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0019] The present invention can effectively control the release and diffusion of metal ions or organic ligands by freezing the metal source solution or organic ligand solution inside the carrier, significantly increase the concentration of metal ions or organic ligands on the carrier surface, thereby further increasing the MOF nucleation density on the carrier surface, and providing a new idea for preparing MOF membranes. By freezing the metal source solution or organic ligand solution inside the carrier, not only the continuity of the membrane is guaranteed, but also the diffusion of organic ligands or metal ions on the outside of the porous carrier into the carrier pores is restricted, thereby inhibiting the nucleation and growth of MOF crystals in the carrier pores, thereby obtaining a MOF membrane with a thinner effective membrane thickness, which is beneficial to the improvement of gas separation performance. The method provided by the present invention has strong universality, low cost, mild conditions, and can be used for large-scale preparation of MOF molecular sieve membranes. The MOF membrane prepared by this method is continuous and dense and exhibits excellent separation performance, such as having higher gas (such as CO 2 / N 2 , CO 2 / CH 4 , C 2 H 4 / C 2 H 6 , C 3 H 6 / C 3 H 8 、nC 4 H 10 / iC 4 H 10 , O 2 / N 2 , H 2 / CO 2 or H 2 / CH4 ) separation performance, and excellent stability, and its application prospects are very broad. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope (SEM) image of the cobalt-based Gallate-MOF membrane prepared in Example 1;

[0021] Figure 2 X-ray diffraction (XRD) pattern of the cobalt-based Gallate-MOF film prepared in Example 1;

[0022] Figure 3 The separation performance stability test results of the cobalt-based Gallate-MOF membrane prepared in Example 1;

[0023] Figure 4 This is a SEM image of the cobalt-based Gallate-MOF membrane prepared in Example 2;

[0024] Figure 5 XRD pattern of the cobalt-based Gallate-MOF film prepared in Example 2;

[0025] Figure 6 This is a SEM image of the cobalt-based Gallate-MOF film prepared in Example 3;

[0026] Figure 7 XRD pattern of the cobalt-based Gallate-MOF film prepared in Example 3;

[0027] Figure 8 This is a SEM image of the cobalt-based Gallate-MOF film prepared in Example 4;

[0028] Fig. 9 XRD pattern of the cobalt-based Gallate-MOF film prepared in Example 4;

[0029] Fig.10 XRD pattern of the cobalt-based Gallate-MOF film prepared in Example 5;

[0030] Fig.11 This is a SEM image of the cobalt-based Gallate-MOF membrane prepared in Example 5;

[0031] Fig.12 This is a SEM image of the cobalt-based Gallate-MOF membrane prepared in Example 6;

[0032] Fig.13 XRD pattern of the cobalt-based Gallate-MOF film prepared in Example 6;

[0033] Fig.14This is a SEM image of the nickel-based Gallate-MOF membrane prepared in Example 7;

[0034] Fig.15 XRD pattern of the nickel-based Gallate-MOF film prepared in Example 7;

[0035] Fig.16 This is a SEM image of the magnesium-based Gallate-MOF film prepared in Example 8;

[0036] Fig.17 XRD pattern of the magnesium-based Gallate-MOF film prepared in Example 8;

[0037] Fig.18 This is a SEM image of the cobalt-based Gallate-MOF film prepared in Example 9;

[0038] Fig.19 XRD pattern of the cobalt-based Gallate-MOF film prepared in Example 9;

[0039] Fig. 20 This is a SEM image of the cobalt-based Gallate-MOF film prepared in Example 10;

[0040] Fig.21 XRD pattern of the cobalt-based Gallate-MOF film prepared in Example 10;

[0041] Fig. 22 is a SEM image of the ZIF-8 membrane prepared in Example 11;

[0042] Fig.23 is the XRD pattern of the ZIF-8 film prepared in Example 11;

[0043] Fig.24 This is a SEM image of the MOF-801 film prepared in Example 12;

[0044] Fig.25 XRD pattern of MOF-801 film prepared in Example 12;

[0045] Fig.26 This is the SEM image of the UiO-66 film prepared in Example 13;

[0046] Fig. 27 XRD pattern of the UiO-66 thin film prepared in Example 13;

[0047] Fig.28 This is a SEM image of a cobalt-based Gallate-MOF membrane prepared without adding a reaction aid in Comparative Example 1;

[0048] Fig.29This is a SEM image of a cobalt-based Gallate-MOF membrane prepared without freezing the metal source solution in Comparative Example 2; DETAILED DESCRIPTION

[0049] The present invention will be further described in conjunction with the following specific examples. However, it should be noted that the present invention is not limited to the following examples.

[0050] Example 1

[0051] Preparation of Cobalt-based Gallate-MOF Membranes by Cryo-Reverse Diffusion Technique

[0052] (1) 0.1 g of cobalt chloride was added to 3 ml of deionized water, and the solution was uniformly dissolved by ultrasonication for 10 min to obtain a metal source solution. The cobalt chloride solution was then injected into an alumina carrier tube sealed at the bottom and frozen in a -23°C freezer for 12 h.

[0053] (2) 0.7 g of gallic acid ligand, 0.18 g of potassium hydroxide and 20 g of deionized water were mixed and stirred to obtain an organic ligand solution.

[0054] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0055] (4) After the reaction in step (3) is completed, the carrier after the reaction is taken out, rinsed with deionized water, and dried at 70° C. for 12 h to obtain a dense and continuous cobalt-based Gallate-MOF membrane.

[0056] Front SEM characterization of cobalt-based Gallate-MOF membranes Figure 1 As shown in Figure 1, the film grows well, the surface is very dense and continuous, there are no significant defects, and the film thickness is 3μm. Figure 2 As shown in Figure 2, the prepared membrane is a pure phase Gallate-MOF membrane. The cobalt-based Gallate-MOF membrane has good C 2 H 4 / C 2 H 6 Separation performance. Among them, C 2 H 4 / C 2 H 6 The separation factor is 7.6, C 2 H 4 The permeation flux is 3.5×10 -8 mol m -2 s -1 Pa -1 .like Figure 3As shown, the prepared Gallate membrane has long-term operational stability. After 50 h of continuous operation, the separation factor and permeation flux remain basically unchanged.

[0057] Example 2

[0058] Preparation of Cobalt-based Gallate-MOF Membranes by Cryo-Reverse Diffusion Technique

[0059] (1) 0.12 g of cobalt nitrate was added to 3 ml of deionized water, and the solution was uniformly dissolved by ultrasonication for 10 min to obtain a metal source solution. The cobalt chloride solution was then injected into an alumina carrier tube sealed at the bottom and frozen in a -23°C freezer for 12 h.

[0060] (2) 0.7 g of gallic acid ligand and 0.18 g of potassium hydroxide were mixed with 20 ml of deionized water and stirred to obtain an organic ligand solution.

[0061] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0062] (4) After the reaction in step (3) is completed, the carrier after the reaction is taken out, rinsed with deionized water, and dried at 70° C. for 12 h to obtain a dense and continuous cobalt-based Gallate-MOF membrane.

[0063] Front SEM characterization of cobalt-based Gallate-MOF membranes Figure 4 As shown in Figure 2, the film grows well, the surface is very dense and continuous, and there are no significant defects. Figure 5 As shown in Figure 2, the prepared membrane is a pure phase Gallate-MOF membrane. The cobalt-based Gallate-MOF membrane has good C 2 H 4 / C 2 H 6 Separation performance. Among them, C 2 H 4 / C 2 H 6 The separation factor is 6.8, C 2 H 4 The permeation flux is 4.1×10 -8 mol m -2 s -1 Pa -1 .

[0064] Example 3

[0065] Preparation of Cobalt-based Gallate-MOF Membranes by Cryo-Reverse Diffusion Technique

[0066] (1) 0.1 g of cobalt chloride was added to 3 ml of deionized water, and the solution was uniformly dissolved by ultrasonication for 10 min to obtain a metal source solution. The cobalt chloride solution was then injected into an alumina carrier tube sealed at the bottom and frozen in a -23°C freezer for 12 h.

[0067] (2) 0.7 g of gallic acid ligand and 0.18 g of sodium hydroxide were mixed with 20 ml of deionized water and stirred to obtain an organic ligand solution.

[0068] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0069] (4) After the reaction in step (3) is completed, the carrier after the reaction is taken out, rinsed with deionized water, and dried at 70° C. for 12 h to obtain a dense and continuous cobalt-based Gallate-MOF membrane.

[0070] Front SEM characterization of cobalt-based Gallate-MOF membranes Figure 6 As shown in Figure 2, the film grows well, the surface is very dense and continuous, and there are no significant defects. Figure 7 As shown in Figure 2, the prepared membrane is a pure phase Gallate-MOF membrane. The cobalt-based Gallate-MOF membrane has good C 2 H 4 / C 2 H 6 Separation performance. Among them, C 2 H 4 / C 2 H 6 The separation factor is 11.2, C 2 H 4 The permeation flux is 3.3×10 -8 mol m -2 s -1 Pa -1 .

[0071] Example 4

[0072] Preparation of Cobalt-based Gallate-MOF Membranes by Cryo-Reverse Diffusion Technique

[0073] (1) 0.1 g of cobalt chloride was added to 3 ml of deionized water, and the solution was uniformly dissolved by ultrasonication for 10 min to obtain a metal source solution. The cobalt chloride solution was then injected into an alumina carrier tube sealed at the bottom and frozen in a -23°C freezer for 6 h.

[0074] (2) Mix 0.7 g of gallic acid ligand, 0.3 ml of ammonia water and 20 ml of deionized water, and stir evenly to obtain an organic ligand solution.

[0075] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0076] (4) After the reaction in step (3) is completed, the carrier after the reaction is taken out, rinsed with deionized water, and dried at 70° C. for 12 h to obtain a dense and continuous cobalt-based Gallate-MOF membrane.

[0077] Front SEM characterization of cobalt-based Gallate-MOF membranes Figure 8 As shown in Figure 2, the cobalt-based Gallate-MOF film is dense, continuous and defect-free. Fig. 9 As shown in Figure 2, the prepared membrane is a pure phase Gallate-MOF membrane. The cobalt-based Gallate-MOF membrane has good C 2 H 4 / C 2 H 6 Separation performance. Among them, C 2 H 4 / C 2 H 6 The separation factor is 9.3, C 2 H 4 The permeation flux is 1.0×10 - 8 mol m -2 s -1 Pa -1 .

[0078] Example 5

[0079] Preparation of Cobalt-based Gallate-MOF Membranes by Cryo-Reverse Diffusion Technique

[0080] (1) 0.1 g of cobalt chloride was added to 3 ml of deionized water, and the solution was uniformly dissolved by ultrasonication for 10 min to obtain a metal source solution. The cobalt chloride solution was then injected into an alumina carrier tube sealed at the bottom, and frozen in a -20°C low-temperature alcohol bath for 6 h.

[0081] (2) 0.7 g of gallic acid ligand and 0.18 g of potassium hydroxide were mixed with 20 ml of deionized water and stirred to obtain an organic ligand solution.

[0082] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0083] (4) After the reaction in step (3) is completed, the carrier after the reaction is taken out, rinsed with deionized water, and dried at 70° C. for 12 h to obtain a dense and continuous cobalt-based Gallate-MOF membrane.

[0084] Front SEM characterization of cobalt-based Gallate-MOF membranes Fig.10 As shown in Figure 2, the cobalt-based Gallate-MOF film is dense, continuous and defect-free. Fig.11 As shown in Figure 2, the prepared membrane is a pure phase Gallate-MOF membrane. The cobalt-based Gallate-MOF membrane has good C 2 H 4 / C 2 H 6 Separation performance. Among them, C 2 H 4 / C 2 H 6 The separation factor is 8.6, C 2 H 4 The permeation flux is 1.2×10 - 8 mol m -2 s -1 Pa -1 .

[0085] Example 6

[0086] Preparation of Cobalt-based Gallate-MOF Membranes by Cryo-Reverse Diffusion Technique

[0087] (1) 0.1 g of cobalt chloride was added to 3 ml of deionized water, and the solution was uniformly dissolved by ultrasonication for 10 min to obtain a metal source solution. The cobalt chloride solution was then injected into an alumina carrier tube sealed at the bottom, and frozen in liquid nitrogen at -196°C for 10 min.

[0088] (2) 0.7 g of gallic acid ligand and 0.18 g of potassium hydroxide were mixed with 20 ml of deionized water and stirred to obtain an organic ligand solution.

[0089] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0090] (4) After the reaction in step (3) is completed, the carrier after the reaction is taken out, rinsed with deionized water, and dried at 70° C. for 12 h to obtain a dense and continuous cobalt-based Gallate-MOF membrane.

[0091] Scanning electron microscopy characterization of the front and cross-section of the cobalt-based Gallate-MOF membrane Fig.12As shown in Figure 2, the cobalt-based Gallate-MOF film is dense, continuous and defect-free. Fig.13 As shown in Figure 2, the prepared membrane is a pure phase Gallate-MOF membrane. The cobalt-based Gallate-MOF membrane has good C 2 H 4 / C 2 H 6 Separation performance. Among them, C 2 H 4 / C 2 H 6 The separation factor is 10.5, C 2 H 4 The permeation flux is 1.5×10 -8 mol m -2 s -1 Pa -1 .

[0092] Example 7

[0093] Preparation of Nickel-based Gallate-MOF Membranes by Cryo-Reverse Diffusion Technique

[0094] (1) 0.05 g of nickel chloride was added to 3 ml of deionized water, and the solution was uniformly dissolved by ultrasonication for 10 min to obtain a metal source solution. The cobalt chloride solution was then injected into an alumina carrier tube sealed at the bottom, and frozen in liquid nitrogen at -196°C for 10 min.

[0095] (2) 0.7 g of gallic acid ligand and 0.18 g of potassium hydroxide were mixed with 20 ml of deionized water and stirred to obtain an organic ligand solution.

[0096] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0097] (4) After the reaction in step (3) is completed, the carrier after the reaction is taken out, rinsed with deionized water, and dried at 70° C. for 12 h to obtain a dense and continuous nickel-based Gallate-MOF membrane.

[0098] Scanning electron microscopy characterization of the front and cross-section of nickel-based Gallate-MOF membranes Fig.14 As shown in Figure 2, the film grows well, the surface is very dense and continuous, and there are no significant defects. Fig.15 As shown in Figure 2, the prepared membrane is a pure phase Gallate-MOF membrane. The Gallate-MOF membrane has good C 2 H 4 / C 2 H 6 Separation performance. Among them, C 2 H4 / C 2 H 6 The separation factor is 7.8, C 2 H 4 The permeation flux is 2.4×10 -8 mol m -2 s -1 Pa -1 .

[0099] Example 8

[0100] Preparation of Magnesium-based Gallate-MOF membranes by cryogenic reverse diffusion technique

[0101] (1) 0.03 g of magnesium chloride was added to 3 ml of deionized water, and the solution was uniformly dissolved by ultrasonication for 10 min to obtain a metal source solution. The cobalt chloride solution was then injected into the sealed alumina carrier tube at the bottom and frozen in liquid nitrogen at -196°C for 10 min.

[0102] (2) 0.7 g of gallic acid ligand and 0.18 g of potassium hydroxide were mixed with 20 ml of deionized water and stirred to obtain an organic ligand solution.

[0103] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0104] (4) After the reaction in step (3) is completed, the carrier after the reaction is taken out, rinsed with deionized water, and dried at 70° C. for 12 h to obtain a dense and continuous magnesium-based Gallate-MOF membrane.

[0105] Scanning electron microscopy characterization of the front and cross-section of the magnesium-based Gallate-MOF membrane Fig.16 As shown in Figure 2, the film grows well, the surface is very dense and continuous, and there are no significant defects. Fig.17 As shown in Figure 2, the prepared membrane is a pure phase Gallate-MOF membrane. The Gallate-MOF membrane has good C 2 H 4 / C 2 H 6 Separation performance. Among them, C 2 H 4 / C 2 H 6 The separation factor is 6.6, C 2 H 4 The permeation flux is 4.2×10 -8 mol m -2 s -1 Pa -1 .

[0106] Example 9

[0107] Preparation of Cobalt-based Gallate-MOF Membranes by Cryo-Reverse Diffusion Technique

[0108] (1) 0.1 g of gallic acid ligand and 0.02 g of potassium hydroxide were mixed with 3 ml of deionized water and stirred to obtain an organic ligand solution. The organic ligand solution was then injected into an alumina carrier tube sealed at the bottom and frozen in liquid nitrogen at -196°C for 10 min.

[0109] (2) 0.5 g of cobalt chloride was added to 15 ml of deionized water and ultrasonicated for 10 min to uniformly dissolve the cobalt chloride to obtain a metal source solution.

[0110] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the metal source solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0111] (4) After the reaction in step (3) is completed, the carrier after the reaction is taken out, rinsed with deionized water, and dried at 70° C. for 12 h to obtain a dense and continuous cobalt-based Gallate-MOF membrane. The front and cross-sectional scanning electron microscopy characterization of the cobalt-based Gallate-MOF membrane is as follows: Fig.18 As shown in Figure 2, the cobalt-based Gallate-MOF film is dense, continuous and defect-free, and the film thickness is 4 μm. Fig.19 As shown in Figure 2, the prepared membrane is a pure phase Gallate-MOF membrane. The cobalt-based Gallate-MOF membrane has good C 2 H 4 / C 2 H 6 Separation performance. Among them, C 2 H 4 / C 2 H 6 The separation factor is 7.5, C 2 H 4 The permeation flux is 2.5×10 -8 mol m -2 s -1 Pa -1 .

[0112] Example 10

[0113] Preparation of Cobalt-based Gallate-MOF Membranes by Cryo-Reverse Diffusion Technique

[0114] (1) 0.1 g of gallic acid ligand and 0.02 g of potassium hydroxide were mixed with 3 ml of deionized water and stirred to obtain an organic ligand solution. The organic ligand solution was then injected into the sealed alumina carrier tube at the bottom and frozen in a -23°C freezer for 6 h.

[0115] (2) 0.5 g of cobalt chloride was added to 15 ml of deionized water and ultrasonicated for 10 min to uniformly dissolve the cobalt chloride to obtain a metal source solution.

[0116] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the metal source solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0117] (4) After the reaction in step (3) is completed, the carrier after the reaction is taken out, rinsed with deionized water, and dried at 70°C for 12 hours to obtain a dense and continuous cobalt-based Gallate-MOF membrane with a thickness of 4 μm. The front and cross-sectional scanning electron microscopy characterization of the cobalt-based Gallate-MOF membrane is as follows: Fig. 20 As shown in Figure 2, the cobalt-based Gallate-MOF film is dense, continuous and defect-free. Fig.21 As shown in Figure 2, the prepared membrane is a pure phase Gallate-MOF membrane. The cobalt-based Gallate-MOF membrane has good C 2 H 4 / C 2 H 6 Separation performance. Among them, C 2 H 4 / C 2 H 6 The separation factor is 7.7, C 2 H 4 The permeation flux is 2.1×10 -8 mol m -2 s -1 Pa -1 .

[0118] Embodiment 11

[0119] Preparation of ZIF-8 membrane by cryo-reverse diffusion technique

[0120] (1) 0.1 g of zinc acetate was added to 3 ml of deionized water, and the solution was uniformly dissolved by ultrasonication for 10 min to obtain a metal source solution. The zinc acetate solution was then injected into an alumina carrier tube sealed at the bottom, and frozen in liquid nitrogen at -196°C for 10 min.

[0121] (2) Mix 0.7 g of imidazole and 0.1 g of sodium acetate with 20 ml of deionized water and stir evenly to obtain an organic ligand solution.

[0122] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0123] (4) After the reaction in step (3) is completed, the carrier is taken out, rinsed with deionized water, and dried at 70° C. for 12 h to obtain a dense and continuous ZIF-8 membrane.

[0124] Front SEM characterization of ZIF-8 membrane Fig. 22 As shown in Figure 2, the film grows well, the surface is very dense and continuous, and there are no significant defects. Fig.23 As shown in Figure 2, the prepared membrane is a pure phase ZIF-8 membrane. The ZIF-8 membrane has good C 3 H 6 / C 3 H 8 Separation performance. Among them, C 3 H 6 / C 3 H 8 The separation factor is 45.3, C 3 H 6 The permeation flux is 1.5×10 -8 mol m -2 s -1 Pa -1 .

[0125] Example 12

[0126] Preparation of MOF-801 membrane by cryogenic reverse diffusion technology

[0127] (1) 0.03 g of zirconium n-propoxide was added to a mixed solution of 2 ml of N,N-dimethylformamide and 1 ml of acetic acid, and the mixture was uniformly dissolved by ultrasonication for 20 min to obtain a metal source solution. The solution was then injected into an alumina carrier tube sealed at the bottom and frozen in liquid nitrogen at -196°C for 10 min.

[0128] (2) Mix 0.04 g of fumaric acid and 20 ml of N,N-dimethylformamide and stir evenly to obtain an organic ligand solution.

[0129] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0130] (4) After the reaction in step (3) is completed, the carrier is taken out, rinsed with ethanol, and dried at 70° C. for 12 h to obtain a dense and continuous MOF-801 membrane.

[0131] Front SEM characterization of MOF-801 membrane Fig.24 As shown in Figure 2, the film grows well, the surface is very dense and continuous, and there are no significant defects. Fig.25As shown in Figure 2, the prepared membrane is a pure phase MOF-801 membrane. The MOF-801 membrane has good CO 2 / CH 4 Separation performance. Among them, CO 2 / CH 4 The separation factor is 25.3, CO 2 The permeation flux is 2.0×10 -7 mol m -2 s -1 Pa -1 .

[0132] Example 13

[0133] Preparation of UiO-66 membrane by cryo-reverse diffusion technique

[0134] (1) 0.03 g of zirconium n-propoxide was added to a mixed solution of 2 ml of N,N-dimethylformamide and 1 ml of acetic acid, and the mixture was uniformly dissolved by ultrasonication for 20 min to obtain a metal source solution. The solution was then injected into an alumina carrier tube sealed at the bottom and frozen in liquid nitrogen at -196°C for 10 min.

[0135] (2) Mix 0.04 g of terephthalic acid and 20 ml of N,N-dimethylformamide and stir evenly to obtain an organic ligand solution.

[0136] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0137] (4) After the reaction in step (3) is completed, the carrier is taken out, rinsed with ethanol, and dried at 70° C. for 12 h to obtain a dense and continuous UiO-66 film.

[0138] Front SEM characterization of UiO-66 film Fig.26 As shown in Figure 2, the film grows well, the surface is very dense and continuous, and there are no significant defects. Fig. 27 As shown in Figure 2, the prepared membrane is a pure phase UiO-66 membrane. The UiO-66 membrane has good CO 2 / N 2 Separation performance. Among them, CO 2 / N 2 The separation factor is 35.3, CO 2 The permeation flux is 3.6×10 -7 mol m -2 s -1 Pa -1 .

[0139] Comparative Example 1 (not according to the present invention)

[0140] (1) 0.1 g of cobalt chloride was added to 3 ml of deionized water, and the solution was uniformly dissolved by ultrasonication for 10 min to obtain a metal source solution. The cobalt chloride solution was then injected into an alumina carrier tube sealed at the bottom, and frozen in liquid nitrogen at -196°C for 10 min.

[0141] (2) Dissolve 0.7 g of gallic acid ligand in 20 ml of deionized water and stir evenly to obtain an organic ligand solution.

[0142] (3) The alumina carrier frozen in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0143] (4) After the reaction in step (3) is completed, the carrier is taken out, rinsed with deionized water, and dried at 70° C. for 12 h.

[0144] The front scanning electron microscopy characterization of the carrier after the reaction is as follows Fig.28 As shown, no Gallate-MOF crystals were formed on the support surface.

[0145] Comparative Example 2 (not according to the present invention)

[0146] (1) 0.1 g of cobalt chloride was added to 3 ml of deionized water, and the solution was uniformly dissolved by ultrasonication for 10 min to obtain a metal source solution. The cobalt chloride solution was then injected into the alumina carrier tube sealed at the bottom.

[0147] (2) Dissolve 0.7 g of gallic acid ligand and 0.18 g of potassium hydroxide in 20 ml of deionized water and stir well to obtain an organic ligand solution.

[0148] (3) The alumina carrier in step (1) is placed in the inner lining of a hydrothermal reactor, and then the organic ligand solution is added, and the reaction is carried out in an oven at 80° C. for 12 hours.

[0149] (4) After the reaction in step (3) is completed, the carrier is taken out, rinsed with deionized water, and dried at 70° C. for 12 h.

[0150] Front SEM characterization of cobalt-based Gallate-MOF membranes Fig.29 As shown, there are a large number of defects on the membrane surface, and the crystals penetrate into the porous support. The membrane thickness is 15 μm.

[0151] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0152] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a metal organic framework membrane using a cryogenic reverse diffusion technique, characterized in that: The invention comprises the following steps: filling a metal source solution inside a porous carrier, freezing the solution, and reacting the solution with an organic ligand; or filling an organic ligand solution inside a porous carrier, freezing the solution, and reacting the solution with a metal source; washing and drying the solution after the reaction is completed to obtain a metal organic skeleton membrane; the freezing temperature is -196 to -20°C; the organic ligand solution or the metal source solution also comprises a reaction aid; the metal element in the metal source is zinc, magnesium, zirconium, iron, cobalt, aluminum, nickel or copper; the organic ligand is an imidazole, carboxylic acid or pyridine ligand; the porous carrier is of sheet type, tubular type or hollow fiber type; the porous carrier is of porous metal oxide, porous metal or porous non-metal oxide; the porous metal oxide is porous aluminum oxide, porous titanium oxide or porous yttrium oxide, the porous metal is porous stainless steel or porous nickel, and the porous non-metal oxide is porous silicon oxide, porous silicon carbide or porous glass.

2. The method for preparing a metal organic framework membrane by cryogenic reverse diffusion technology according to claim 1, characterized in that: The freezing method is quick freezing or slow freezing, and the freezing time is 1 min~120 h.

3. The method for preparing a metal organic framework membrane by cryogenic reverse diffusion technology according to claim 1, characterized in that: The solvent in the organic ligand solution or the metal source solution is water, methanol, ethanol, N, N-dimethylformamide, N, N-diethylformamide, dimethyl sulfoxide or propanol.

4. The method for preparing a metal organic framework membrane by cryogenic reverse diffusion technology according to claim 1, characterized in that: The molar ratio of the organic ligand to the metal source is organic ligand / metal source=0.1-5.

5. The method for preparing a metal organic framework membrane by cryogenic reverse diffusion technology according to claim 1, characterized in that: The reaction aid is an alkaline or acidic reagent.

6. The method for preparing a metal organic framework membrane by cryogenic reverse diffusion technology according to claim 1, characterized in that: The molar ratio of the reaction aid to the metal source is reaction aid / metal source=0.01-1.

7. The method for preparing a metal organic framework membrane by cryogenic reverse diffusion technology according to claim 1, characterized in that: The reaction temperature is 20-180°C and the reaction time is 1 min-120 h.

8. A metal organic framework membrane prepared by the method of claim 1 in CO2 / N2, CO2 / CH4, C2H4 / C2H6, C3H6 / C3H8, n-C4H 10 / i-C4H 10 , O2 / N2, H2 / CO2 or H2 / CH4 separation.

Citation Information

Patent Citations

  • Method for in-situ preparation of MOFs@f-GO hybrid membrane by freeze-drying technology

    CN109173730A

  • Method for preparing ZIF-L grains through freezing technology

    CN110540655A